2004
DOI: 10.1002/agr.20007
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of direct mail coupon usage revisited: Evidence from count panel data models

Abstract: This report employs count panel (as opposed to cross-sectional) data to empirically investigate the determinants of direct-mail coupon use. We focus on comparing the coupon use discrepancies between national and store dairy brands. The results do not support the main hypothesis that participants use more coupons the longer they stay in the coupon program. Evidence also shows that prior use significantly explains the coupon-redemption behavior, while it is found that there are significant expiration date and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Various studies found that distance to the redemption site negatively influences the chances of redemption (Chiou-Wei and Inman, 2008;Danaher et al, 2015;Beeck and Toporowski, 2017). Travelling long distances to redeem coupons requires spending more time and resources on redemption, which reduces the attractiveness of coupon redemption (Hongjai Rhee and Bell, 2002;Chiou-Wei, 2004). In this study, distance has been considered a moderator.…”
Section: Moderatorsmentioning
confidence: 92%
“…Various studies found that distance to the redemption site negatively influences the chances of redemption (Chiou-Wei and Inman, 2008;Danaher et al, 2015;Beeck and Toporowski, 2017). Travelling long distances to redeem coupons requires spending more time and resources on redemption, which reduces the attractiveness of coupon redemption (Hongjai Rhee and Bell, 2002;Chiou-Wei, 2004). In this study, distance has been considered a moderator.…”
Section: Moderatorsmentioning
confidence: 92%